2021
DOI: 10.1136/bmjdrc-2020-001924
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions for type 2 diabetes management among migrants and ethnic minorities living in industrialized countries: a systematic review and meta-analyses

Abstract: The objective of this systematic review was to determine the effectiveness of lifestyle interventions to improve the management of type 2 diabetes mellitus (T2DM) among migrants and ethnic minorities. Major searched databases included MEDLINE (via PubMed), EMBASE (via Ovid) and CINAHL. The selection of studies and data extraction followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. In the meta-analysis, significant heterogeneity was detected among the studies (I2 >50%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
3
15
0
2
Order By: Relevance
“…The analysis according to the type of intervention delivery revealed that group interventions had a statistically significant effect on HbA1c levels (SMD, -0.28; p=0.010), and this effect was higher than interventions with other types of delivery. This result aligns with a previous meta-analysis showing that group interventions were better at optimizing outcomes for diabetes [ 44 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…The analysis according to the type of intervention delivery revealed that group interventions had a statistically significant effect on HbA1c levels (SMD, -0.28; p=0.010), and this effect was higher than interventions with other types of delivery. This result aligns with a previous meta-analysis showing that group interventions were better at optimizing outcomes for diabetes [ 44 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Commitment refers to the cognitive and emotional factors that empower people to use the health resources that are available to them [ 35 , 48 ]. Commitment needs to be demonstrated by the user over time, and may be stimulated through social support and intellectual resources to encourage behavior changes toward improving the individual’s health status [ 35 ].…”
Section: Strategies To Improve Engagement With Self-management Interv...mentioning
confidence: 99%
“…Commitment needs to be demonstrated by the user over time, and may be stimulated through social support and intellectual resources to encourage behavior changes toward improving the individual’s health status [ 35 ]. An example of commitment in chronic disease management is the use of health coaching for people with diabetes, where the health professional plays the role of a coach to facilitate the individual in developing strategies to manage their chronic illness rather than telling the individual what to do [ 48 ].…”
Section: Strategies To Improve Engagement With Self-management Interv...mentioning
confidence: 99%
“…Indeed, lifestyle interventions among migrant groups and ethnic minorities appear to be only moderately effective in lowering the HbA1c value [57]. A recent systematic review with meta-analysis also finds that lifestyle interventions with peer support have positive effects on clini cal outcomes such as the HbA1c value, as well as on the knowledge and practices of diabetes self-management [59].…”
Section: Training and Counseling Materialsmentioning
confidence: 99%